ความรุนแรงเชิงโครงสร้างในการทำงานของผู้หญิง: กรณีศึกษาในจังหวัดขอนแก่น/The Structural Violence in The Work of Women: A case of Khon Kaen province, Thailand - มหิวรรณ ปิยะกมล; อายุวัฒน์ ดุษฎี (Journal of Humanities and Social Sciences (HUSOKKU), 2019)
The purpose of this study was to investigate the level of the structural violence and the factors influencing the structural violence in the work of women. The quantitative methodology was employed with individual level as a unit of analysis. The sample consisted of 398 women who are working in government agencies and private enterprise. The samples were randomly by multi-stage sampling technique in 9 municipals of Khon Kaen province. The data were collected using the interview schedule from May to June 2018 and analyzed by descriptive statistics and multiple regression (multi-level) analysis. The results revealed that the most of women samples (55.5 percentages) were in the Generation Y (19-38 years old) and the average age was 37.6 years old. 51.3 percentages of women sample are married, and 43.7 percentages got bachelor’s degrees or higher degrees. They are working (39.9 percentages) in large organizations (more than 200 workers) and 40.7 percentages of the women samples have worked more than 10 years. The result showed that 23.9 percentages of women samples got the structural violence in the work at a rather high level and high level (combined). There were 4 factors that influenced to structural violence in the work of women at statistically significant 0.05 level, included the medium organization, the understanding of female worker’s rights, socialization of gender roles, and self-efficacy in work. All independent variables can explain the variation of structural violence in the work of women at 27.1 percentages (R2= 0.271).